PENGENDALIAN DAN PENGELOLAAN TIM LINTAS FUNGSIONAL DALAM ORGANISASI - Supardi . (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2008)
The complexity of modern business and the need for quick responses to changing conditions don’t allow employees to go through channels anymore. But many companies have a hard time combining information, action and interpretation across old structural boundaris, like hierarchical organization. Often, the result is decisions so untimely as to be irrelevant, no matter how technically correct they are. In today’s business environment, companies need the team concept to increase productivity and profitability, enhance quality, beat competition, or achieve the company objective du jour. Cross-functional teams (CFTs) have increased in use within a variety of organizations. While these teams claim to enhance organizational effectiveness, research has seen mixed results. This paper examines the challenges faced by CFTs and why these challenges facilitate the need for the development of a teams climate for trust.Keyword: cross-functional team, hierarchical organization